Alteration of liver immunity by increasing inflammatory response during co-administration of methamphetamine and atazanavir. (3rd May 2020) - Li, Yanfei; Li, Sangsang; Xia, Yang; Li, Xiangrong; Chen, Tingjun; Yan, Jie; Wang, Yong
Abstract: Objective: Use of methamphetamine (METH) is prevalent among HIV-infected individuals. Previous research has shown that both METH and HIV protease inhibitors exert influences on mitochondrial respiratory metabolism and hepatic nervous system. This study aims to study the joint effect of METH and HIV protease inhibitors on hepatic immune function. Materials and methods: Based on the differentially expressed genes obtained from RNA-seq of the liver from mouse model, the expression levels of CD48 and Macrophage Receptor with Collagenous Structure (MARCO) were examined using qRT-PCR and flow cytometry, and the expression and secretion of cytokines IL-1β, IL-6, IL-8, IL-10, IFN-γ, IFN-β, and TNF-α were determined using qRT-PCR and ELISA in THP-1-derived macrophages. Results: Our results indicated that compared with the control group, CD48 molecules were significantly down-regulated by METH–atazanavir co-treatment, and the expression level of CD48 decreased as METH concentration increases. MARCO molecules were increased, especially at larger doses of METH and atazanavir treatment. In addition, in the presence of METH–atazanavir, the expression and secretion of a series of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and IL-8 increased while the expression and secretion of anti-inflammatory cytokine IL-10 decreased. Conclusion: These results demonstrated that METH and atazanavir had a combined impact on the liver immunity, suggesting that the co-treatment could enhance inflammatory response and suppress NK cell activation via CD48.